Characterization of a Family of Arabidopsis Genes Related to Xyloglucan Fucosyltransferase1 - Sarria, Rodrigo (American Society of Plant Physiologists, 2001)
To understand primary cell wall assembly in Arabidopsis, we have focused on identifying and characterizing enzymes involved in xyloglucan biosynthesis. Nine genes (AtFUT2–10) were identified that share between 47% and 62% amino acid similarity with the xyloglucan-specific fucosyltransferase AtFUT1. Reverse transcriptase-PCR analysis indicates that all these genes are expressed. Bioinformatic analysis predicts that these family members are fucosyltransferases, and we first hypothesized that some may also be involved in xyloglucan biosynthesis. AtFUT3, AtFUT4, and AtFUT5 were expressed in tobacco (Nicotiana tabacum L. cv BY2) suspension culture cells, and the resulting proteins did not transfer fucose (Fuc) from GDP-Fuc to tamarind xyloglucan. AtFUT3, AtFUT4, and AtFUT5 were overexpressed in Arabidopsis plants. Leaves of plants overexpressing AtFUT4 or AtFUT5 contained more Fuc than wild-type plants. Stems of plants overexpressing AtFUT4 or AtFUT5 contained more xylose, less arabinose, and less galactose than wild-type plants. We suggest that the AtFUT family is likely to include fucosyltransferases important for the synthesis of wall carbohydrates. A targeted analysis of isolated cell wall matrix components from plants altered in expression of these proteins will help determine their specificity and biological function.